Risk of malignancy in adenomas detected during screening colonoscopy - Rösch, Thomas; Brenner, Hermann (Clinical gastroenterology and hepatology, 2018)
Background & Aims - A higher incidence of proximal interval cancers after colonoscopy has been reported in several follow-up studies. One possible explanation for this might be that proximally located adenomas have greater malignant potential. The aim of the present study was to assess the risk of malignancy in proximal versus distal adenomas in patients included in a large screening colonoscopy database; adenoma shape and the patients’ age and sex distribution were also analyzed. - Methods - Data for 2007-2012 from the German National Screening Colonoscopy Registry, including 594,614 adenomas identified during 2,532,298 screening colonoscopies, were analyzed retrospectively. The main outcome measure was the rate of high-grade dysplasia (HGD) in adenomas, used as a surrogate marker for the risk of malignancy. Odds ratios (ORs) for the rate of HGD found in adenomas were analyzed in relation to patient- and adenoma-related factors using multivariate analysis. - Results - HGD histology was noted in 20,873 adenomas (3.5%). Proximal adenoma locations were not associated with a higher HGD rate. The most significant risk factor for HGD was adenoma size (OR 10.36 ≥1 cm vs <1 cm), followed by patient age (OR 1.26 and 1.46 for age groups 65-74 and 75-84 vs 55-64 years) and sex (OR 1.15 male vs female). In comparison with flat adenomas as a reference lesion, sessile lesions had a similar HGD rate (OR 1.02) and pedunculated adenomas had a higher rate (OR 1.23). All associations were statistically significant (P ≤ .05). - Conclusions - In this large screening database, it was found that the rates of adenomas with HGD are similar in the proximal and distal colon. The presence of HGD as a risk marker alone does not explain higher rates of proximal interval colorectal cancer. We suggest that certain lesions (flat, serrated lesions) may be missed in the proximal colon and may acquire a more aggressive biology over time. A combination of endoscopy-related factors and biology may therefore account for higher rates of proximal versus distal interval colorectal cancer.